Principles of Distinguishing Nuclear, Semi-Peripheral, Peripheral and Beyond-Peripheral Zones in the Structure of Verbal Semantic Field «Agricultural Production (Crop Production)» - Познанський, Роман Васильович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The principles of distinguishing nuclear, semi-peripheral, peripheral and beyond-peripheral zones in the structure of verbal semantic field «agricultural production (crop production)» on the basis of «importance» in this semantic structure of the seme «nomination of action, process or state directly or indirectly related to crop production» are highlighted in the article. The analysis of classification criteria of referring one or another verb to the semantic field «agricultural production (crop production)» to the appropriate zone is done on given examples.